Accelerated dobutamine stress testing: Safety and feasibility in patients with known or suspected coronary artery disease - Lu, David (Clin Cardiol, 2009)
Background: Dobutamine pharmodynamics require approximately 10 min to reach steady state. Despite this, standard dobutamine stress echo typically uses 3‐min stages of advancing dobutamine doses because of safety concerns. Hypothesis: In patients with a high pretest probability of coronary artery disease (CAD), a continuous infusion of high‐dose dobutamine is a feasible and safe method for performing a dobutamine stress test. Methods: Forty‐seven consecutive patients (mean age 64 ± 11 years) with 3.0 ± 1.4 cardiac risk factors underwent dobutamine stress testing utilizing a single, high‐dose (40 mcg/kg/min), continuous dobutamine infusion. The 40 mcg/kg/min infusion was continued for up to 10 min or until a test end‐point had been reached. If a test endpoint was not achieved, atropine (up to 1.0 mg) was added. Results: Heart rate rose from 71 ± 12 to 137 ± 18 beats/min at peak (p< 0.0001) with a concomitant change in systolic blood pressure (143 ± 35 vs. 167 ± 38 mmHg; p = 0.001) but no change in diastolic blood pressure (74 ± 19 vs. 75 ± 18 mmHg; p = NS). Target heart rate was achieved in 20 of 47 (43%) patients with accelerated dobutamine alone and in 34 of 47 (72%) with the addition of atropine. An average of 11.6 ± 3.7 min was required to obtain target heart rate. Subjective sensations from the dobutamine occurred in 49% of patients (palpitations 21%, nausea 6%, chest pain 6%, headache 6%, dizziness 13%), mild arrhythmia in 48% of patients (ventricular premature beats 38%, supraventricular tachycardia 10%), and one patient had nonsustained ventricular tachycardia. Conclusion: A single, high‐dose (40 mcg/kg/min) dobutamine‐atropine protocol provides an efficient means of performing dobutamine stress echocardiography with a similar symptom profile as conventional dobutamine infusion protocols in patients with a high pretest probability of CAD. Randomized, controlled studies will be necessary to assess the sensitivity and specificity of this accelerated dobutamine echo protocol.